perancangan desain kemasan premium village leather berbasis kayu dan resin sebagai upaya menungkatkan brand awareness - Saputro, Dwi Cahyo Ponco; Riyanto, Darwin Yuwono; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2017)
The purpose of designing the packaging premium Village Leather based on the wood and resin is to increase brand awareness. The research done by using qualitative research methods by doing interviews, observation and documentation, and study of the library to get data that is used as a supporter of the making of the concept of design promotion media. The data has been analyzed using several stages, i.e. data reduction, presentation of data and the conclusions. From the analysis of the data found some key words that refers to the communication strategy promotional media that will be used to reach the target audiance intended. After the analysis of the data, clean the concept of keyword or design premium packaging design that is